Mechanochemical synthesis of corannulene: scalable and efficient preparation of a curved polycyclic aromatic hydrocarbon under ball milling conditions - Báti, Gábor (2023)
Corannulene, a curved polycyclic aromatic hydrocarbon, is prepared in a multigram scale through mechanochemical synthesis. Initially, a mixer mill approach is examined and found to be suitable for a gram scale synthesis. For larger scales, planetary mills are used. For instance, 15 g of corannulene could be obtained in a single milling cycle with an isolated yield of 90 %. The yields are lower when the jar rotation rate is lower or higher than 400 revolutions per minute (rpm). Cumulatively, 98 g of corannulene is produced through the ball milling-based grinding techniques. These results indicate the future potential of mechanochemistry in the rational chemical synthesis of highly curved nanocarbons such as fullerenes and carbon nanotubes.